Em nome do povo de Deus: o significado de ser evangélico no tempo da política / In the name of God's people: the meaning of being evangelical in the time of politics - Santiago Filho, Elio Roberto Pinto (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2012)
Este artigo tem por objetivo estudar a relação entre os evangélicos e a política. Enfatiza-se a dimensão simbólica dessa relação no intuito de perceber as recentes transformações que têm ocorrido no campo evangélico. Por meio de um trabalho de campo, visualizou-se essa dinâmica em nível local, relacionando o material recolhido com a bibliografia especializada. A hipótese em questão é que o tempo da política determina uma temporalidade religiosa, influindo em uma unidade conjuntural do campo evangélico. Mas essa unidade, na verdade, deve ser percebida mais profundamente na própria dinâmica do campo religioso brasileiro na consolidação da figura de um tipo médio protestante, considerado genericamente como evangélico. Busca-se, pois, compreender o comportamento político dos evangélicos por meio dessa ótica, em que estão inclusas transformações identitárias e simbólicas. Abstract This article aims to study the relationship between evangelicals and politics. We emphasize the symbolic dimension of this relationship to understand the recent changes that have occurred in the evangelical field. Through field work, this dynamics is viewed at the local level, relating the material collected with the specialized literature. The hypothesis in question is that the time of the politics establishes a religious temporality, influencing a conjunctural unity of the evangelical field. But this unity, in fact, should be more deeply seen into the dynamics of the Brazilian religious field, in the consolidation of the figure of an average protestant type, generally regarded as evangelical. The aim is, therefore, to understand the political behavior of the evangelicals through this perspective, which includes symbolical and identitary transformations.